APLIKASI TEKNOLOGI ISOTOP ALAM UNTUK ANALISIS POLA ALIRAN AIRTANAH MENUJU DESA KADILANGU SEBAGAI STUDI AWAL PENCEMARAN AIRTANAH OLEH TEMPAT PEMAKAMAN UMUM KAUMAN KECAMATAN DEMAK KABUPATEN DEMAK - , GAGAD RAHMADI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Demak subdistrict has an average water table that is less than 2 meters so that the wells in the District of Demak prone to be contaminated by pollutants originating from the cemetery. It is because the cemetery in Indonesia has an average depth of approximately 2 meters. The primary objective of this study was to determine the utilization of natural isotopic pattern of groundwater flow toward the Kadilangu and determine the effect of contamination by Kauman Cemetery (TPU Kauman) on the quality of groundwater in the Kadilangu village. In this research the analysis of deuterium (2H) and oxygen-18 (18O) is used to determine the genesis of groundwater. Analysis of indicators of pollution carried in two points, the point before and after the flow of groundwater pass the TPU Kauman. Pollution indicators used are CaCO3, SO4-2 and PO4-P. The results of the analysis showed groundwater flow from the recharge area around Mangunjiwan to Kadilangu have the same genesis. An increase in the level of pollutants in Kadilangu which flow from groundwater of Mangunjiwan after passing TPU Kauman is observed. Of three of the pollutant indicators mentioned before, only level of CaCO3 that is above the threshold value of drinking water set by the government of the Republic of Indonesia, that is 840 mg/l.